Enhanced Cellular Entry and Efficacy of Tat Conjugates by Rational Design of the Auxiliary Segment - Zhang, Pengcheng (American Chemical Society, 2014)
[Image: see text] Conjugation with a cell penetrating peptide such as Tat presents an effective approach to improve the intracellular accumulation of molecules with low membrane permeability. This strategy, however, leads to a reduced cellular entry of molecules that can cross cell membrane effectively. We report here that covalent linkage of an additional hydrophobic unit that mimics a hydrophobic domain near the Tat sequence can further improve the cellular uptake of the parental conjugate into cancer cells regardless of the membrane permeability of the unconjugated molecule. Both fluorescent imaging and flow cytometry measurements confirmed the effect of palmitoylation on the increased internalization of the Tat conjugates with either 5-carboxyfluorescein (5-FAM), a nonmembrane penetrating dye, or doxorubicin, an anticancer cancer drug that can readily diffuse across cell membranes. In the case of the Tat–doxorubicin conjugate, palmitoylation improves the conjugate’s anticancer activity in both drug sensitive and resistant cervical cancer cell lines. We further demonstrate that modification of a Tat–5-FAM conjugate with a hydrophobic quencher could not only efficiently quench the fluorescence outside of cancer cell but also facilitate its entry into MCF-7 breast cancer cells. These results highlight the importance of rational molecular design of using peptide conjugation chemistry in cancer therapeutics and diagnostics.